Pengaruh Arang Sekam Padi dan Pupuk NPK Terhadap Pertumbuhan Bibit Kakao(Theobroma cacao L.) - Mhd. Rizki Hidayu; Wardati Wardati; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of interaction of several doses of rice husk charcoal and NPK fertilizer to the growth of cocoa seedlings and to get the best dose of fertilizer from rice husk charcoal for the growth of cocoa seedlings (Theobroma cacao L.) This research has been carried out in the Technical Implementation Unit of the Garden Trial Faculty of Agriculture University of Riau, Bina Widya Road, Simpang Baru Village Tampan District, Pekanbaru City. This study lasted for four months starting from May until August 2016. This research is a 3x3 factorial experiment prepared according to a complete randomized design (RAL). The treatment in this research is: first factor is rice husk charcoal consisting of 3 levels: A0 = Without giving of rice husk charcoal, A1 = 1 kg of rice husk charcoal per polybag and A2 = 2 kg of rice husk charcoal per polybag. The second factor is NPK fertilizer consisting of 3 levels: P0 = No NPK fertilizer, P1 = 15 g NPK fertilizer per polybag and P2 = 30 g NPK fertilizer per polybag. This study consisted of 9 treatment combinations, and repeated 3 times so that there were 27 experimental units. Each experimental unit consists of 3 plants, so the total plant is 81 plants. The data obtained were analyzed statistically by using vocabulary. The variance was then tested further by Duncan's multiple-range test of 5%. The parameters observed were cocoa seed height, stem diameter, leaf number, leaf area, root volume, root canopy ratio and dry weight of plant. The results showed that the interaction of several doses of rice husk charcoal and NPK fertilizer gave no significant effect on stem diameter, leaf number, leaf area, root volume, dry weight and root ratio of cocoa seedlings. The interaction treatment of rice huskcharcoal 2 kg per polybag and NPK dosage 30 g per polybag tends to give effect to the parameters of plant height and stem diameter while the parameter of leaf number does not occur tendency increase.Keywords: Cocoa seeds, rice husk charcoal, NPK fertilizer